The effect of various types of forest fires on pine resin productivity in Gunung Walat University Forest, Sukabumi, Indonesia (Biodiversitas Journal of Biological Diversity, 2017)
Prasetya CD, Syaufina L, Santosa G. 2017. The effect of various types of forest fires on pine resin productivity in GunungWalat University Forest, Sukabumi, Indonesia. Biodiversitas 18: 476-482. Gunung Walat University Forest (GWUF) of Sukabumi,Indonesia is one of pine resin producers that has 71 hectares of resin production area. The forest fire burned 7 hectares of resinproduction area in August 2015 was expected to affect the resin productivity. The aim of this study was to analyze the effect of eachtype of forest fire to pine resin productivity and analyze the correlation between the biophysic aspect and pine resin productivity afterthe fire. The types of forest fire were litter and shrub fire, stem fire, and crown fire. ANOVA test showed that the types of forest firehave significant effect to resin production with the value of Ftable (3.12)
Keywords: Fire effect; pine resin; productivity